Operative Mitral and Tricuspid Valve Surgery - Moorjani, Narain (Springer London, 2018)
This book reviews the surgical management of the mitral and tricuspid valves. It provides a detailed examination of the recent exponential improvements in the understanding of the pathophysiology of the disease processes affecting these valves, which has resulted in significant changes in the strategies that can be applied. Chapters include analysis of the basic sciences related to the anatomy and physiology of the mitral and tricuspid valves, pre-operative imaging of these valves, illustrating the variety of pathologies encountered, and critically a comprehensive step-by-step approach to the peri-operative management and surgical techniques pertaining to each pathological process. Operative Mitral and Tricuspid Valve Surgery systematically covers all major topics involved in the current practice of an adult cardiac surgeon who performs operations on the mitral and tricuspid valves. It is therefore suitable for the cardiac intensive care unit specialist interested in improving their knowledge of cardiac patient management. It is an essential resource for all adult cardiac surgeons and cardiac intervention specialists at any stage of their career.